Black identity, education and resistance practices: a decolonial reading in an urban quilombo - Mirianne Santos de Almeida; Ilka Miglio de Mesquita (Universidade Federal de Santa Catarina, 2019)
From the lenses of decolonial thinking and ethnographic making in a submissive locus, stage of struggle and resistance - the urban quilombo 'Maloca', located in the Sergipe capital - We analyze the actions developed in the project Criliber (Child - Freedom), directed to the formation of the black child's identity. Our goal was to understand the behavior of a historically marginalized group and how they faced racism. The theoretical reference is based on Homi Bhabha (1998), Stuart Hall (2003) and Catharine Walsh (2013) who problematize the maintenance of the remnants of colonization and recognize, in the articulation of marginalized groups, different possibilities of descontinue coloniality. In an attempt to break free from the currents of colonization, the actions of Criliber have echoed to strengthen the sense of belonging and self-affirmation of black identity.